2020
DOI: 10.1371/journal.pone.0238658
|View full text |Cite
|
Sign up to set email alerts
|

Digitally engaged physicians about the digital health transition

Abstract: Background Digitalisation affects 90% of healthcare. Digital health, however, does not only refer to technological transformation but also has considerable cultural and social consequences. It fundamentally reshapes the roles of physicians and patients, as well as their relationship. Moreover, from the second half of the 20th century, the growing number of chronic patients and the increase in life expectancy have posed new challenges to the medical workforce. Objectives To explore the digitally engaged physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 32 publications
(51 reference statements)
2
30
0
4
Order By: Relevance
“…This factor had been significant ( P <.001) in the bivariate analysis and showed a very similar trend for an effect like attitudes in the multivariable analysis, but lost significance once attitudes were controlled for. For one thing, due to their clinical experience, health care professionals might feel more certain about specific effects of eHealth for patients than for the hospital or work conditions in general [ 25 ]. Additionally, physicians’ and nurses’ professional role identity as patient advocates might make the function of eHealth tools to serve patients’ needs particularly salient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This factor had been significant ( P <.001) in the bivariate analysis and showed a very similar trend for an effect like attitudes in the multivariable analysis, but lost significance once attitudes were controlled for. For one thing, due to their clinical experience, health care professionals might feel more certain about specific effects of eHealth for patients than for the hospital or work conditions in general [ 25 ]. Additionally, physicians’ and nurses’ professional role identity as patient advocates might make the function of eHealth tools to serve patients’ needs particularly salient.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, perceived costs/negative consequences did not seem to make a difference. This finding does, however, not imply that perceived costs might be similarly irrelevant when it comes to actual adoption [ 13 , 25 ]. General willingness might mainly require a positive motivation or a clear rationale in favor of change while costs might become more apparent once actual experience is initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IT-enabled transformation does not always proceed as desired [40], as working practices in hospitals have not greatly changed in the last few decades. Although the technological possibilities have matured and investments continue to rise [64], collaboration is still conducted with common, proven instruments [65].…”
Section: Lesson 1: Organizational Change Requires Alignment Of the Mindsetmentioning
confidence: 99%
“…Another reason is that findings often are discrepant [8,9,[12][13][14]18,19,21,22]. For instance, many studies in the European region found low adoption rates when national strategies for the introduction of electronic medical records were first implemented [13,15,23], but some saw improvements over time [14,24], while others did not [12,25].…”
Section: Introductionmentioning
confidence: 99%